2007
DOI: 10.1002/cncr.23175
|View full text |Cite
|
Sign up to set email alerts
|

Development of sorafenib and other molecularly targeted agents in hepatocellular carcinoma

Andrew X. Zhu

Abstract: It is well appreciated that hepatocellular carcinoma (HCC) represents one of the most challenging malignancies of worldwide importance. In fact, HCC is the fifth most common cancer and the third most common cause of cancer-related death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
11

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 57 publications
0
73
0
11
Order By: Relevance
“…There is, therefore, a strong rationale for targeting growth factors that drive the angiogenic process as a potential therapeutic strategy for the treatment of HCC. VEGF is a key angiogenic factor, and several agents that target VEGF or VEGFR are currently in development for the treatment of HCC (Table 1) Bevacizumab (Avastin; Genentech, Inc., South San Francisco, CA, USA) is a recombinant, humanized, anti-VEGF monoclonal antibody (Presta et al, 1997) that has shown encouraging early evidence of efficacy in patients with advanced HCC (Siegel et al, 2008;Zhu, 2008). In two small monotherapy studies, treatment with bevacizumab 5-10 mg/kg resulted in partial response (PR) in 8-13% of patients and stable disease (SD) in 54-72% of patients (Malka et al, 2007;Siegel et al, 2008).…”
Section: Therapeutic Targets In Hccmentioning
confidence: 99%
“…There is, therefore, a strong rationale for targeting growth factors that drive the angiogenic process as a potential therapeutic strategy for the treatment of HCC. VEGF is a key angiogenic factor, and several agents that target VEGF or VEGFR are currently in development for the treatment of HCC (Table 1) Bevacizumab (Avastin; Genentech, Inc., South San Francisco, CA, USA) is a recombinant, humanized, anti-VEGF monoclonal antibody (Presta et al, 1997) that has shown encouraging early evidence of efficacy in patients with advanced HCC (Siegel et al, 2008;Zhu, 2008). In two small monotherapy studies, treatment with bevacizumab 5-10 mg/kg resulted in partial response (PR) in 8-13% of patients and stable disease (SD) in 54-72% of patients (Malka et al, 2007;Siegel et al, 2008).…”
Section: Therapeutic Targets In Hccmentioning
confidence: 99%
“…Hepatocellular carcinoma is so infrequent in children that these patients have often been treated according to hepatoblastoma regimens, albeit with far less success. Recently, sorafenib, a multikinase inhibitor, was approved by the U.S. Food and Drug Administration for the first-line treatment of hepatocellular carcinoma after a study in adults demonstrated efficacy in advanced-stage hepatocellular carcinoma [44], but no data exist on its use in children. The approach to treatment of less common malignant tumors of the liver parallels the approach to the tumors with similar histology, that is, a primary hepatic sarcoma is generally treated like sarcomas in other anatomical sites.…”
Section: Treatmentmentioning
confidence: 99%
“…9,10 These include derangements in the regulation of signal transduction pathways involved cell proliferation (Ras/Raf/MEK/ERK pathway) apoptosis and protein synthesis (PI3/AKT/mTOR pathway). 11 Angiogenesis also plays an important role in tumorigenesis because HCC is highly vascular.…”
Section: Commentmentioning
confidence: 99%